554 Cerebral Emboli Detection Using Robotic Transcranial Doppler With Artificial Intelligence During Transcatheter Aortic Valve Replacement - A Novel and Autonomous Neuromonitoring Tool. (April 2023) - Baig, Ammad; Manion, Christopher; Khawar, Wasiq; Donnelly, Brianna; Monteiro, Andre; Iyer, Vijay; Levy, Elad I.; Siddiqui, Adnan Hussain
Abstract : INTRODUCTION: Periprocedure ischemic stroke remains a serious complication in patients undergoing transcatheter aortic valve replacement (TAVR). METHODS: Consecutive patients undergoing TAVR were prospectively enrolled in the study. Basic demographics and procedural details, such as protection device used, type of aortic valve used, and any intraprocedure or postprocedure (<30 days) complications, were recorded. Continuous variables were analyzed by two-sample Mann-Whitney t-test and categorical variables by chi-square or Fisher test. RESULTS: Thirty-one patients were prospectively enrolled (mean age=79.9±7.6 years; men=16 [51.6%]). Hyperlipidemia was present in 27 patients (87.1%), followed by hypertension in 25 (80.6%). Mean aortic valve area was 0.7 cm 2 . Mean aortic-ventricular gradient was 43 mmHg (interquartile range 31.5-50 mmHg). The protection device was used in 16 cases. A significantly lower emboli count was observed in the protection group (means of 470.38 vs. 693.33 in the non-protection group; P=0.01). Emboli counts during valve positioning and implantation were significantly different as well (means of 249.92 protection vs. 387.5 non-protection; P=0.01). One (4%) nonfatal stroke was seen postoperatively in the protection group. CONCLUSIONS: We describe use of a novel real-time intraoperative neuromonitoring tool in patients undergoing TAVR. Significantly fewer HITS were detected in the protection group. Valve positioning and implantation was identified as the most significant stage in terms of intraprocedural HITS.